Promoting Aid Effectiveness from the Bottom up with ICTs - Figuéres, Caroline; Senmartin, Denise; Eugelink, Hilde (World Bank, 2012)
The article offers examples of projects sponsored by IICD in Africa and latin America that confirm the lasting impact of ICT on poverty alleviation.